Analisis Bibliometrik Riset Pemasaran Media Sosial: Peran AI dan Teknologi Emerging dalam Perilaku Konsumen - Hanifa Sri Nuryani (SENTRI: Jurnal Riset Ilmiah, 2026)
This study presents a systematic bibliometric analysis exploring the evolution of social media marketing research, emphasizing the integration of artificial intelligence (AI) and emerging technologies in shaping consumer behavior between 2015 and 2025. Utilizing the rigorous PRISMA protocol, the research analyzes 70 high-impact articles from the Scopus and Sinta databases, carefully triangulated with credible secondary data from leading global industry reports. Through VOSviewer visualization, four primary thematic clusters are identified: AI Evolution and Personalization, Immersive Technologies in Marketing, Dynamics of Digital Consumer Behavior, and Data Ethics and Privacy. The findings reveal a definitive paradigm shift from reactive automation to generative AI, which fundamentally drives hyper-personalization and fosters co-creative brand-consumer relationships. Furthermore, immersive technologies, particularly the Metaverse, are increasingly redefined as seamless phygital layers rather than isolated virtual environments. Crucially, the study highlights the privacy paradox as a central dilemma, noting that modern consumers demand highly personalized experiences while remaining profoundly skeptical regarding data utilization. This phenomenon occurs alongside the growing dominance of short-form videos and user-generated content. Ultimately, this research contributes theoretically by mapping the interdisciplinary nexus of digital marketing, behavioral psychology, and managerial accounting. To maximize practical utility, marketing practitioners are strongly advised to establish a robust trust architecture prioritizing algorithmic transparency and explicit value exchange to ethically navigate the privacy paradox.